Pengembangan Media Pembelajaran Permainan Ludo Pada Muatan IPA Untuk Siswa Kelas IV SD IT Suralaga - Rosdatul Pawazah; Muhammad Sururuddin; Mijahamuddin Alwi; Dina Fadilah; Musabihatul Kudsiah (STKIP Melawi, 2023)
Abstract: This study aims to develop ludo game, is a learning media on the science content of fourth grade students. This study uses the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The results of media validation is in the